Factors influencing use of long-acting versus short-acting contraceptive methods among reproductive-age women in a resource-limited setting - Tibaijuka, Leevan; Odongo, Robert; Welikhe, Emma; Mukisa, Wilber; Kugonza, Lilian; Busingye, Imelda; Nabukalu, Phelomena; Ngonzi, Joseph; Asiimwe, Stephen B.; Bajunirwe, Francis (BMC Women's Health, 2017)
Unplanned pregnancy remains a common problem in many resource-limited settings, mostly due to limited access to modern family planning (FP) services. In particular, use of the more effective long-acting reversible contraceptive (LARC) methods (i.e., intrauterine devices and hormonal implants) remains low compared to the short-acting methods (i.e., condoms, hormonal pills, injectable hormones, and spermicides). Among reproductive-age women attending FP and antenatal care clinics in Uganda, we assessed perceptions and practices regarding the use of modern contraceptive methods. We specifically aimed to evaluate factors influencing method selection.We performed a mixed-methods cross-sectional study, in which we administered structured interviews to 180 clients, and conducted 4 focus group discussions (FGDs) with 36 clients and 8 in-depth personal qualitative interviews with health service providers. We summarized quantitative data and performed latent content analysis on transcripts from the FGDs and qualitative interviews.The prevalence of ever use for LARC methods was 23%. Method characteristics (e.g., client control) appeared to drive method selection more often than structural factors (such as method availability) or individual client characteristics (such as knowledge and perceptions). The most common reasons for choosing LARC methods were: longer protection; better child-spacing; and effectiveness. The most common reasons for not choosing LARC methods included requiring a client-controlled method and desiring to conceive in the near future. The most common reasons for choosing short-acting methods were ease of access; lower cost; privacy; perceived fewer side effects; and freedom to stop using a method without involving the health provider. The personal characteristics of clients, which appeared to be important were client knowledge and number of children. The structural factor which appeared to be important was method availability.Our results suggest that interventions to improve uptake of LARC among reproductive age women in this setting should consider: incorporating desired method-characteristics into LARC methods; targeted promotion and supply of LARC; and increased counselling, sensitization, and education.
Keywords: Long-acting reversible contraceptives (LARC), Short-acting contraceptives, Method selection, Factors, Resource-limited setting